2020
DOI: 10.1371/journal.pgen.1008561
|View full text |Cite
|
Sign up to set email alerts
|

FLS2 is a CDK-like kinase that directly binds IFT70 and is required for proper ciliary disassembly in Chlamydomonas

Abstract: Intraflagellar transport (IFT) is required for ciliary assembly and maintenance. While disruption of IFT may trigger ciliary disassembly, we show here that IFT mediated transport of a CDK-like kinase ensures proper ciliary disassembly. Mutations in flagellar shortening 2 (FLS2), encoding a CDK-like kinase, lead to retardation of cilia resorption and delay of cell cycle progression. Stimulation for ciliary disassembly induces gradual dephosphorylation of FLS2 accompanied with gradual inactivation. Loss of FLS2 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…Ciliary disassembly in Chlamydomonas can be induced experimentally by treatment of the cells with 20 mM NaPPi, a calcium chelator. , Under this condition, cilia are gradually disassembled around 3 h and cells become immotile. Thus, cilia motility can be used as a readout for ciliary disassembly.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ciliary disassembly in Chlamydomonas can be induced experimentally by treatment of the cells with 20 mM NaPPi, a calcium chelator. , Under this condition, cilia are gradually disassembled around 3 h and cells become immotile. Thus, cilia motility can be used as a readout for ciliary disassembly.…”
Section: Resultsmentioning
confidence: 99%
“…NaPPi induced ciliary disassembly involves two CDK-like kinases, FLS1 and FLS2. , We then tested whether abemaciclib inhibited FLS1, which undergoes phosphorylation with a gel shift during NaPPi induced ciliary disassembly. As shown in Figure e, abemaciclib indeed inhibited FLS1 phosphorylation induced during ciliary disassembly.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In support of a central role for KIF24 in cilium disassembly, a recent study identified FLS2 as a CDK-like kinase that phosphorylates the KIF24 ortholog CrKIF13 in Chlamydomonas, allowing efficient cilia disassembly (Figure 2D; Zhao et al, 2020). In turn, phosphorylated FLS2 showed lower activity and appears to be dephosphorylated upon cilia disassembly when it enters cilia by binding to the IFT-B component IFT70 (Zhao et al, 2020).…”
Section: Cilium Disassemblymentioning
confidence: 90%